On the particle–particle contact effects on the hole cleaning process via a CFD–DEM model. (1st November 2016) - Akhshik, Siamak; Behzad, Mehdi; Rajabi, Majid
ABSTRACT: The accurate and precise computational models in order to predict the hole cleaning process is one of the helpful assets in drilling industries. Besides the bulk properties such as the flow velocity, particles average size, cleaning fluid properties, etc., that will affect the cleaning process, there is an unanswered question about the microscopic properties of the particles, particularly those which determines the contact characteristics: Do those play a major role or not? The rudimentary answer is not. The first purpose of the present work is to answer this question via a developed computational fluid dynamics coupled with discrete element method (CFD–DEM) in which the six unknown rolling and sliding friction coefficients of particle–particle contact, particle–wall contact, and particle–drill contact are considered as the main microscopic properties of the contacts. The second purpose is to search for optimum values of these coefficients in order to calibrate the CFD–DEM model with the experimental data for a near horizontal well cleaning available in the literature. The verification of the calibrated CFD–DEM model is checked by simulation of the hole cleaning process for different inclination angles of the deviated well. The results indicate the pivotal role of the microscopic properties of the particles on the characteristics of the particle transport mechanism.